The reality of inclusion in physical education in the Brazilian school system: facts, theories and practice - Castro, Eliane Mauerberg de; Figueiredo, Gabriella Andreetta; Campbell, Debra Frances (Revista Brasileira de Educação Física e Esporte, 2020)
Our purpose in this article was threefold. First, we attempted to analyze evidences of inclusion in the Brazilian school, and we argued that inclusion still is a long road ahead, particularly, in the field of physical education. In relation to inclusion, we used data provided by the Brazilian government itself to demonstrate several issues of concern, including some with educational governing bodies. Second, we examined how the Brazilian physical education national curriculum parameters have been tailored in their pedagogical recommendations to accommodate the “movement culture” approach. Although physical educators endorsed the new curricular directives, their practice in school with inclusion revealed troublesome situations. Overall, they admitted that they did not feel prepared to work with students with disability in their classes, and they feel that they need continuing education, as well as actual administrative/government investments. Third, we introduced concepts from dynamic systems theory to our adapted physical education practice while working with people with disabilities in inclusive settings. We illustrated the theory in its application to the physical education practices by reporting a lifetime of work in outreach programs in the field of adapted physical activity (APA), at São Paulo State University at Rio Claro. The complexities in the practice of inclusive school physical education require a holistic approach, which we feel can be accomplished through the employment of dynamic systems concepts. Whether epistemological directions include the movement culture approach or dynamic systems theory, or a hybrid, these efforts must be sustained by committed teachers, the school system, government leaders, families, and the entire community.